2021
DOI: 10.1177/0894439321994232
|View full text |Cite
|
Sign up to set email alerts
|

Website Defacer Classification: A Finite Mixture Model Approach

Abstract: Hackers often engage in website defacement early in their criminal careers to establish a reputation. Some hackers become increasingly prolific and launch a large number of attacks against their targets, whereas others only launch a few attacks before eventually desisting from a life of crime. A better understanding of why some hackers launch a large number of attacks, while others do not, will assist in the implementation of targeted intervention strategies. Therefore, the current study, using a sample of 119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Crime research has repeatedly shown that large proportions of crime and deviant behavior tend to concentrate in a few places, times, targets, and offenders. While much research has been dedicated to the study of the concentration of crime for traditional crime, there is a need to expand research about the concentration of cybercrime in digital spaces of interaction (e.g., Rhumorbarbe et al, 2018;Zarras et al, 2014), times of the day and days (e.g., Kemp et al, 2021;Williams et al, 2019), victims and targets (e.g., Holt et al, 2020;Leukfeldt and Yar, 2016), and offenders (e.g., Burruss et al, 2021;Décary-Hétu and Giammoni, 2017;van de Weijer et al, 2021). In this research we accessed a large dataset of 186,735 reports of cybercrimes involving ransom requests and fraudulent payments through Bitcoin (i.e., ransomware, blackmail scam, sextortion, darknet market fraud, and Bitcoin tumbler fraud), and analyzed the concentration of crimes in Bitcoin addresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crime research has repeatedly shown that large proportions of crime and deviant behavior tend to concentrate in a few places, times, targets, and offenders. While much research has been dedicated to the study of the concentration of crime for traditional crime, there is a need to expand research about the concentration of cybercrime in digital spaces of interaction (e.g., Rhumorbarbe et al, 2018;Zarras et al, 2014), times of the day and days (e.g., Kemp et al, 2021;Williams et al, 2019), victims and targets (e.g., Holt et al, 2020;Leukfeldt and Yar, 2016), and offenders (e.g., Burruss et al, 2021;Décary-Hétu and Giammoni, 2017;van de Weijer et al, 2021). In this research we accessed a large dataset of 186,735 reports of cybercrimes involving ransom requests and fraudulent payments through Bitcoin (i.e., ransomware, blackmail scam, sextortion, darknet market fraud, and Bitcoin tumbler fraud), and analyzed the concentration of crimes in Bitcoin addresses.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of online cryptomarkets, Christin (2014) observed that a few sellers concentrate large proportions of items advertised, Décary-Hétu and Giammoni (2017) showed evidence of concentration of buyers' feedback on a small percentage of drug dealers, and Munksgaard et al (2019) argue that a few tobacco traffickers concentrate very large market shares in cryptomarkets. And recent research has also found strong signs of offending concentration among a few website defacement offenders (Burruss et al, 2021;van de Weijer et al, 2021).…”
Section: The Concentration Of Cybercrimementioning
confidence: 97%
See 1 more Smart Citation
“…Their findings could help build more resilient systems by matching security measures with the underlying motivations and technical capacity of attackers. Burruss et al (2021) adopt a finite mixture modeling approach to understand what differentiates prolific hackers from more occasional online offenders. They expand our range of malicious hacker classification tools by examining how attack frequency, social media presence, and attack content (such as political statements, music, pictures and animations) can help predict the intensity of future attack patterns.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…This special issue originates from the Leiden conference, organized in 2019 by Vrije Universiteit Amsterdam and the Hague University of Applied Sciences, and where five of the seven articles included in this volume were first presented and discussed (Banerjee et al, in press ; Burruss et al, in press ; Cross & Layt, in press ; Dupont & Lusthaus, in press ; van der Bruggen & Blokland, in press ). Two more articles were submitted independently but reflect the same concern for a deeper understanding of the role the human factor plays in cybercrime, with a particular focus on victims’ experiences and needs (Borwell et al, in press ; Fissell et al, in press ).…”
mentioning
confidence: 99%